The Impact of Work-family Conflict on the Well-being of Employees in Chinese Private Enterprises - Liu, Xiaozhen (2020)
Work-family conflict has attracted more scholars’ attention in contemporary organisations. Any imbalance between work and family can cause conflict and affect personal well-being negatively, which is prominent among Chinese private companies. However, the existing literature rarely focuses on Chinese private enterprises. This research aims to evaluate how work-to-family conflict and family-to-work conflict are associated with work satisfaction, family satisfaction and psychological distress, to discuss the impact of work-family conflict on the well-being of employees in Chinese private enterprises.